PENGETAHUAN USIA LANJUT TENTANG POSYANDU LANSIA DI DUSUN MANDUNG DESA SEMBUNG GEDE KECAMATAN KERAMBITAN KABUPATEN TABANAN TAHUN 2018 - Ni Made Ari Febriyanti (STIKES ADVAITA MEDIKA TABANAN, 2020)
Background and objectives: Elderly is an aging process with increasing age of individuals which is marked by a decrease in the function of organs such as the brain, heart, liver and kidneys as well as an increase in loss of active body tissue in the form of body muscles. Posyandu for elderly is the center of community activities in the effort to provide health services for the elderly. This study aims to determine the knowledge of the elderly about the Elderly Posyandu in Mandung Hamlet, Sembung Gede Village, Kerambitan District, Tabanan Regency. Methods: This study is a descriptive study with a cross sectional approach. The number of samples taken was 41 respondents with a purposive sampling approach technique. The instrument used in this study was filling out a questionnaire with 15 statements in accordance with the theoretical concept of knowledge to be measured. The analysis technique in this study uses univariate analysis where each variable will be described based on the percentage results. Result: elderly knowledge about posyandu for elderly, most of the two respondents (67%) have less knowledge from basic education, most of the two respondents (67%) have less knowledge of 75-90 years old and all respondents, namely three (100%) have lack of knowledge to get information sources from electronic media. Conclusion: Most of the elderly have less knowledge about posyandu for the elderly, most of the elderly have less knowledge of 75-90 years old and all of them have less knowledge of getting information sources from electronic media